Routine minimalist transcatheter aortic valve implantation with local anesthesia only. Issue 10 (October 2020) - Saia, Francesco; Palmerini, Tullio; Marcelli, Chiara; Chiarabelli, Matteo; Taglieri, Nevio; Ghetti, Gabriele; Negrello, Fabio; Moretti, Carolina; Bruno, Antonio Giulio; Compagnone, Miriam; Corsini, Anna; Castelli, Andrea; et al.
Abstract : Aims: Conscious sedation instead of general anesthesia has been increasingly adopted in many centers for transfemoral transcatheter aortic valve replacement (TAVR). Improvement of materials and operators' experience and reduction of periprocedural complications allowed procedural simplification and adoption of a minimalist approach. With this study, we sought to assess the feasibility and safety of transfemoral TAVR routinely performed under local anesthesia without on-site anesthesiology support. Methods: The routine transfemoral TAVR protocol adopted at our center includes a minimalist approach, local anesthesia alone with fully awake patient, anesthesiologist available on call but not in the room, and direct transfer to the cardiology ward after the procedure. All consecutive patients undergoing transfemoral TAVR between January 2015 and July 2018 were included. We assessed the rates of actual local anesthesia-only procedures, conversion to conscious sedation or general anesthesia and 30-day clinical outcomes. Results: Among 321 patients, 6 received general anesthesia upfront and 315 (98.1%) local anesthesia only. Mean age of the local anesthesia group was 83.2 ± 6.9 years, Society of Thoracic Surgery score 5.8 ± 4.8%. A balloon-expandable valve was used in 65.7%. Four patients (1.3%) shifted to conscious sedation because of pain or anxiety; 6 patients (1.9%) shifted to general anesthesia because of procedural complications. Hence, local anesthesia alone was possible in 305 patients (96.8% of the intended cohort, 95% of all transfemoral procedures). At 30 days, in the intended local anesthesia group, mortality was 1.6%, stroke 0.6%, major vascular complications 2.6%. Median hospital stay was 4 days (IQR 3–7). Conclusion: Transfemoral TAVR can be safely performed with local anesthesia alone and without an on-site anesthesiologist in the vast majority of patients.